Design of a Telegram Chatbot to Control Internet Connection on Computer Laboratory - Wildanil Ghozi; Elkaf Rahmawan P.; Oki Setiono (Institute of Computer Science (IOCS), 2022)
Colleges with majors in computer science have a large number of computer labs to support practicum. Each laboratory room has several practicum classes per day. Moreover, each practicum requires different software and internet connection. Software can be prepared at pre-lecture. But the internet needs to be configured every class starts. A staff is stationed in each room to serve the needs of the practicum. However the staff does not have access rights to the router to configure the internet. To maintain network security, routers can only be managed by the network administrator. This requires staff to ask the network administrator to turn the internet on or off and to increase bandwidth limit. This interaction takes time so that the performance of the laboratory is poor. To solve this problem, we designed an internet controller bot as a bridging system between laboratory staff and routers. This chatbot provides limited router features needed by staff. So that the router's vital features cannot be accessed by staff. This system has been successfully developed so that staff can fulfill requests from lecturers to turn on/off the internet, check bandwidth consumption and increase bandwidth limit quickly.